Molecular epigenetic switches in neurodevelopment in health and disease - Hoffmann, Anke; Zimmermann, Christoph A.; Spengler, Dietmar (Frontiers in Behavioral Neuroscience, 2015)
Epigenetic mechanisms encode information above and beyond DNA sequence and play a critical role in brain development and the long-lived effects of environmental cues on the pre- and postnatal brain. Switch-like, rather than graded changes, illustrate par excellence how epigenetic events perpetuate altered activity states in the absence of the initial cue. They occur from early neural development to maturation and can give rise to distinct diseases upon deregulation. Many neurodevelopmental genes harbor bivalently marked chromatin domains, states of balanced inhibition, which guide dynamic ‘ON or OFF’ decisions once the balance is tilted in response to developmental or environmental cues. Examples discussed in this review include neuronal differentiation of embryonic stem cells into progenitors and beyond, activation of Kiss1 at puberty onset, and early experience-dependent programming of Avp, a major stress gene. At the genome-scale, genomic imprinting can be epigenetically switched on or off at select genes in a tightly controlled temporospatial manner and provides a versatile mechanism for dosage regulation of genes with important roles in stem cell quiescence or differentiation. Moreover, retrotransposition in neural progenitors provides an intriguing example of an epigenetic-like switch, which is stimulated by bivalently marked neurodevelopmental genes and possibly results in increased genomic flexibility regarding unprecedented challenge. Overall, we propose that epigenetic switches illuminate the catalyzing function of epigenetic mechanisms in guiding dynamic changes in gene expression underpinning robust transitions in cellular and organismal phenotypes as well as in the mediation between dynamically changing environments and the static genetic blueprint.